The Differential Impact of Covid-19 on Gender (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Pandemics and outbreaks have differential impacts on women and men. From risk of exposure and biological susceptibility to infection to the social and economic implications, individuals’ experiences are likely to vary according to their biological and gender characteristics and their interaction with other social determinants. Because of this, global and national strategic plans for COVID-19 preparedness and response must be grounded in strong gender analysis and must ensure meaningful participation of affected groups, including women and girls, in decision-making and implementation. WHO has declared it as pandemic as it has hit the world infecting a large number of people and causing large number of deaths. The government has imposed lockdown all over the world due to the serious issue, but now it is leading to negative impact on people in the form of economic and health impacts. This paper aims to examine the impact of Covid-19 on gender, especially working men and women. The paper examines various secondary sources of data like literature and articles to generalize the findings. It has been found from the study that the effect is more on women than on men. India as a developing country is also facing the problem with economy. Thus steps should be taken by the government to improve the social, political and economic systems related to pre-existing equalities.